Design of Domain Structure and Realization of Ultralow Thermal Conductivity for Record-High Thermoelectric Performance in Chalcopyrite - Zhang, Jian (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.